Transit: An analysis of networked criminal groups and criminal opportunities at transit ports - Casey, Ryan Nicole (Cogent social sciences, 2017)
Like the path of many contraband commodities, trafficked cultural objects cross countless legal borders and intersect with the legitimate market world at a number of critical transit junctures, which supports the concept of a single “grey” market. These transit settings, where different elements of trafficking networks must converge, are sites of vulnerability for criminals and opportunity for law enforcement intervention. For this discussion, the case study of Subhash Kapoor’s trafficking network will be used as a frame of reference throughout the essay to support the idea that a port, as an interface in the global supply chain, is a critical site for analysis and understanding of international trafficking in cultural objects. What follows is a discussion of conceptualisations of organised crime in late modernity, a spatial analysis of the global cultural heritage trade, and an overview of the securitisation and role of sea ports in trade